Decomposition of CO₂ Emissions over 1980-2003 in Turkey - Wietze Lise (Fondazione Eni Enrico Mattei (FEEM), 2005)
There is a multi-dimensional need for studying the energy situation in Turkey and to ob-tain insight into the development of CO2 emissions. On the one hand, recent projections of the OECD show that Turkey has a yearly GDP growth potential of over 7%. On the other hand, recent projections of UNDP and World Bank indicate that the level of CO2 emission is going to rise six-fold by 2025 with respect to the level of emissions in 1990. It is a great challenge to both meet the growth target and keep the CO2 under control. Thereupon, this paper tries to unfold factors that explain CO2 emissions by undertaking a complete decomposition analysis for Turkey over the period 1980 2003. The analysis shows, as is common to relatively fast growing economies, that the biggest contributor to the rise in CO2 emissions is the expansion of the economy (scale effect). The carbon intensity and the change in composition of the economy, which nearly move in tandem, also contribute to the rise in CO2 emissions, albeit at a slower rate. The energy intensity of the economy, which is decreasing, is responsible for a modest reduction in CO2 emissions. Hence, in congruence with the scale effect, we do not find a decoupling of carbon emissions and economic growth in Turkey over the period 1980 2003.
Keywords: Q4; Q54; 330; Decomposition analysis; Turkey; Energy; CO2 emissions; Economic growth